Spatio-temporal dynamics of grassland ecosystem services and the segmentation effects of their drivers: A case in South China Karst - Yongyao Li; Kangning Xiong; Wenfang Zhang; Shuai Xiang; Baoshan Zhang; Rong Li (Global Ecology and Conservation)
Maintaining grassland stock and improving its ecosystem services (ES) are critical yet challenging for ecological and economic sustainability. However, the diversity and spatial heterogeneity of global grasslands pose significant challenges to studying the spatio-temporal coupling characteristics of grassland area and ES changes, especially in the karst desertification control (KDC) regions. This study quantified the grassland area, grassland ES, and the elasticity of grassland ES in response to changes in grassland area within the KDC region of South China. The Moran index was applied to analyze spatio-temporal evolution characteristics, and a quantile regression model was used to explored the segmentation effects of influencing factors. Results showed that: (1) During 2000–2020, despite a 4.36 % decrease in grassland area (399,205 hm2) within the KDC region of South China, the comprehensive index of grassland ES increased from 0.99 to 1.03. Furthermore, counties where the elasticity index of grassland ES exceeded 1 constituted 73.52 %, indicating a general improvement in ES supply capacity. (2) Factors influencing grassland ES in the KDC region demonstrated clear segmentation effects, with the intensity and direction of the same factors varying significantly across different thresholds. The significance of socio-economic factors has been increasing steadily. (3) Within the framework of the UN Decade on Ecosystem Restoration 2021–2030, differentiated ecological engineering measures should be tailored based on the specific constraints of grassland ES in the KDC region. Our research results open a new perspective for the study of the impact mechanism of grassland ES. It can enrich the understanding of grassland ES and offer valuable insights to guide future initiatives for ecosystem restoration and sustainable development in ecologically fragile, particularly karst, areas.